Persepsi Masyarakat Mengenai Fenomena Kotak Kosong Dalam Pemilihan Kepala Daerah Kabupaten Bangka Tahun 2024: Penelitian - Agus Sofyan; Irfan Afendi; Batin Galang Putera (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2026)
This study aims to analyze public perception of the phenomenon of empty boxes in the 2024 Bangka Regency Regional Head Election (Pilkada), which was carried out with only one pair of candidates. The phenomenon of empty boxes is a concern because it reflects the condition of local democracy that lacks competition and causes various perceptions and political attitudes of the community. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews with election organizers (KPU and Bawaslu) as well as several voters from four different sub-districts. The results of the study show that public perception is influenced by three main indicators: political attention, political understanding, and political evaluation. The level of political attention tends to decrease in rural areas due to a lack of information and a sense of interest in the electoral process. The public's political understanding of the meaning of empty boxes is still low, especially related to the constitutional rights of voters in facing a single candidate. Political evaluations of the Pilkada system and existing candidates vary, ranging from critical to apathetic. This study recommends the need to improve political literacy, wider and more equitable socialization, and evaluation of candidacy regulations so that local democracy can run more representative and participatory.